Venous thromboembolism and subsequent permanent work-related disability - Brækkan, Sigrid K. (J Thromb Haemost, 2016)
BACKGROUND: The burden of venous thromboembolism (VTE) related to permanent work-related disability has never been assessed among a general population. Therefore, we aimed to estimate the risk of work-related disability in subjects with incident VTE compared with those without VTE in a population-based cohort. METHODS: From the Tromsø Study and the Nord-Trøndelag Health Study (HUNT), Norway, 66005 individuals aged 20–65 years were enrolled in 1994–1997 and followed to December 31, 2008. Incident VTE events among the study participants were identified and validated, and information on work-related disability was obtained from the Norwegian National Insurance Administration database. Cox-regression models using age as time-scale and VTE as time-varying exposure were used to estimate hazard ratios (HR) with 95% confidence intervals (CI) adjusted for sex, BMI, smoking, education level, marital status, history of cancer, diabetes, cardiovascular disease and self-rated general health. RESULTS: During follow-up, 384 subjects had a first VTE and 9862 participants were granted disability pension. The crude incidence rate of work-related disability after VTE was 37.5 (95%CI: 29.7–47.3) per 1000 person-years, versus 13.5 (13.2–13.7) per 1000 person-years among those without VTE. Subjects with unprovoked VTE had a 52% higher risk of work-related disability than those without VTE (HR 1.52, 95%CI 1.09–2.14) after multivariable adjustment, and the association appeared to be driven by deep vein thrombosis. CONCLUSION: VTE was associated with subsequent work-related disability in a cohort recruited from the general working-age population. Our findings suggest that indirect costs due to loss of work time may add to the economic burden of VTE.